Design and Development of Platform Deployment Arm (PDA) for Boiler Header Inspection at Thermal Power Plant by Using the House of Quality (HOQ) Approach - Ismail I.N.; Halim K.A.; Sahari K.S.M.; Anuar A.; Jalal M.F.A.; Syaifoelida F.; Eqwan M.R. (Elsevier B.V., 2023)
Houses; Inspection; Intelligent control; Professional aspects; Repair; Robotics; Smart sensors; Thermoelectric power plants; Customer requirements; Design and Development; House of Quality; Inspection robots; Platform Deployment Arm (PDA); Repair and maintenance; Technical aspects; Thermal power plants; Boilers